Modelagem numérica do perfil térmico e do escoamento de material termoplástico por extrusão em um cabeçote customizado para manufatura aditiva - Santos, André Luiz Grando (2024)
This work presents a procedure for modeling and numerical analysis of the flow of a thermoplastic fluid with pseudoplastic behavior applied to a custom miniature vertical head based on twin-screw extrusion for additive manufacturing. It is a case study conducted using the miniature head of an innovative prototype conceived on a laboratory scale for direct manufacturing using the PP RP141 raw material in powder form. The temperature profiles in the head were estimated, and the techniques adopted were validated with experimental data from a prototype of the extruder head. The pressures and flow details in the channels forming the extrusion nozzle (die) were revealed through a 3D model. The dimensionless parameters characteristic of the types of elements that constitute the screws were also determined by a 3D model. A 1D flow model published by another author was modified and coded to predict the pressures and, consequently, the location of the fully filled sections of the screws. This modified model was validated by comparison with documented cases in the literature. Furthermore, the filled sections were simulated using mesh immersion techniques in a 3D model, and details of the complex flow in these sections were discussed. Finally, a comparison of the pressures predicted by the modified 1D model with those obtained by the 3D model revealed a good approximation between the results of these analyses using the technique proposed in this work, thus establishing a procedural roadmap for exploring the processing limits of the unit, screw compositions, process variables, and materials, as well as aiding decision-making in the design stages of other units and improvements of this innovative variant of additive manufacturing.